Mouthwash Potential of Ethanol Extract of Ajwa Date Seeds (Phoenix dactylifera L.) against Porphyromonas gingivalis Bacteria - Mauriska Nada Silmi Almisky; Etny Dyah Harniati; Steffi Triany Arnov; Ariyani Faizah (Journal of Indonesian Dental Association, 2026)
Introduction: Periodontal disease is a major oral health problem worldwide, with Porphyromonas gingivalis recognized as one of the primary causative bacteria. Ajwa date seeds (Phoenix dactylifera L.) have potential for development as a natural mouthwash due to their antibaterial properties, which are attributed to various bioactive compounds, including flavonoids, tannins, and saponins. Objective: To evaluate the antibacterial effect of a mouthwash containing ethanol extract of ajwa date seeds (Phoenix dactylifera L.) against the growth of Porphyromonas gingivalis. Methods: This laboratory experimental study employed a post-test-only control group design. The samples were divided into five groups: a positive control, a negative control, and three treatment groups receiving mouthwash containing ethanol extract of ajwa date seeds at concentrations of 3.25%, 6.5%, and 12.5%. Antibacterial activity was evaluated using the disc diffusion method on Mueller–Hinton Agar (MHA), with six replicates for each group. Data were analyzed using one-way ANOVA followed by Tukey's Honestly Significant Difference (HSD) post hoc test. Results: Mouthwash containing ethanol extract of ajwa date seeds inhibited the growth of Porphyromonas gingivalis, as demonstrated by the formation of inhibition zones around the discs. A concentration-dependent increase in the diameter of the inhibition zone was observed. The mean inhibition zone diameters were 10.175 mm, 12.300 mm, and 14.442 mm for the 3.25%, 6.5%, and 12.5% extract concentrations. Conclusion: Mouthwash containing ethanol extract of ajwa date seeds (Phoenix dactylifera L.) significantly inhibited the growth of Porphyromonas gingivalis. The antibacterial activity in 12.5% concentration demonstrating the greatest inhibitory effect.